Electronic interface for Lidar system and smart cities applications - Pantoli, Leonardo (Array, 2019)
This work deals with the design of a new readoutelectronics for silicon photomultipliers sensors. The so-calledSiPMs sensors are an emerging technology currentlydiffusing in many applications and, among them, in thedefinition of a new generation of LIDAR systems. Thelatter, nowadays have a primary role in the evolutionprocess that is involving Smart Cities, being an enablingtechnology in different fields. The solution here proposed isrealized at electronic level with a 150 nm technology processfrom LFoundry and results provide a feasibledemonstration of the capability of the proposed designapproach to be employed in practical application.